The Role of Financial Creative activities to achieve Entrepreneurial Orientation dimensions - jabar, dilshad habib (Humanities Journal of University of Zakho, 2018)
The research dealt with the subject of the activities of financial creative represented by the activity of financing and management of risks and liquidity, the research also touched Dimensions of the Entrepreneurial Orientation approach of innovation and risk taking and proactive. The study aims to examine the role of financial creative to achieve the dimensions of the Entrepreneurial Orientation, it has been selected exchange and Money transferring offices (bureau) in Duhok province to conduct field side of the search, which included research (44) of the leaders of these offices, and adopted the researchers questionnaire form after It has been confirmed validity and reliability as a tool head for the collection of field data side, data were analyzed using standard deviations and simple linear regression analysis of the Pearson correlation coefficient.